2019
DOI: 10.1038/s41598-019-50344-4
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran supplementation modulates growth, microbiota and metabolome in weaning infants: a clinical trial in Nicaragua and Mali

Abstract: Rice bran supplementation provides nutrients, prebiotics and phytochemicals that enhance gut immunity, reduce enteric pathogens and diarrhea, and warrants attention for improvement of environmental enteric dysfunction (EED) in children. EED is a subclinical condition associated with stunting due to impaired nutrient absorption. This study investigated the effects of rice bran supplementation on weight for age and length for age z-scores (WAZ, LAZ), EED stool biomarkers, as well as microbiota and metabolome sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 88 publications
0
60
0
Order By: Relevance
“…The global nontargeted metabolomics was performed through Metabolon, Inc. The extraction method has been described previously (33). Briefly, 80% methanol was added on plasma and urine in a ratio of 300 mL solvent per 100 mg plasma or urine.…”
Section: Plasma and Urine Extraction For Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global nontargeted metabolomics was performed through Metabolon, Inc. The extraction method has been described previously (33). Briefly, 80% methanol was added on plasma and urine in a ratio of 300 mL solvent per 100 mg plasma or urine.…”
Section: Plasma and Urine Extraction For Metabolomicsmentioning
confidence: 99%
“…Plasma and urine are ideal biological fluids to examine the physiologic effects of dietary exposures and have shown sensitivity to detect subtle and major changes in metabolite abundance over time (32,33). A nontargeted metabolite approach was applied herein to assess metabolic modulation of colorectal cancer risk following increased navy bean intake.…”
Section: Introductionmentioning
confidence: 99%
“…If so, this would suggest that a rice bran dietary intervention should be used for the chemoprevention of CRC in those who have a high risk of developing this disease. Furthermore, only a few human studies have examined the effects of a rice bran dietary intervention on the intestinal microbiota [15][16][17][18], and only one was conducted in a Chinese population [17]. As the composition of the intestinal microbiota has been shown to differ across ethnicities [19], possibly due to lifestyle and genetic factors that may affect the microbiome composition [20,21], the intake of rice bran is likely to exhibit different effects on the intestinal microbiota of individuals of different ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few in vivo studies have highlighted its effect on gut microbiota and the reports have striking differences. In a clinical trial, Zambrana et al, (2019) showed significant enrichment of Veillonella, Megasphaera and Dialister species at the genus level from gut samples of children from either Nicaragua or Mali at 12 months’ time (24). Another study by Sheflin et al, (2015) showed a significant increase in the abundance of Methanobrevibacter smithii, Paraprevotella clara, Ruminococcus flavefaciens, Dialister succinatiphilus, Bifidobacterium sp., Clostridium glycolicum, Barnesiella intestinihominis, Anaerostipes caccae and Ruminococcus bromii OTUs after heat stabilized rice bran was fed to people (3 g/day) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple studies corroborating the beneficial effect of rice bran and quercetin on the host, their effect on microbiota varies significantly from study to study and has lower taxonomic resolution (22, 24-26). Variation in in vivo studies are due to multiple compounding host-related factors which makes it difficult to interpret microbiome results precisely (27).…”
Section: Introductionmentioning
confidence: 99%